2011
DOI: 10.5511/plantbiotechnology.10.0823c
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of guaiacyl/p-hydroxyphenyl lignin in Arabidopsis thaliana T87 cells

Abstract: Abstruct Arabidopsis thaliana is the most widely used model plant in the area of plant biosciences, and the cell line T87 is one of the most commonly used lines in Arabidopsis cell cultures. The characteristics of lignins in cultured cells often differ from those of lignins in intact plants. To date, nothing is known about the lignins of T87 cells. In this study, we characterized lignins of T87 cells using six analytical methods; phloroglucinol staining, thioacidolysis, nitrobenzene oxidation, alkaline hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Inner part and outer part: the inner and outer parts of 1st internode, respectively. only of β-O-4 substructure which is obtained by the thioacidolysis but also of other substructures, each organ was analysed by the microscale nitrobenzene oxidation method (Yamamura et al 2010(Yamamura et al , 2011. The GC-MS analysis of the nitrobenzene oxidation products showed that lignin in each organ consisted of guaiacyl, syringyl, and p-hydroxyphenyl units (Table 2), consistent with the result of thioacidolysis.…”
Section: Lignin Structures Of E Ravennaementioning
confidence: 63%
See 2 more Smart Citations
“…Inner part and outer part: the inner and outer parts of 1st internode, respectively. only of β-O-4 substructure which is obtained by the thioacidolysis but also of other substructures, each organ was analysed by the microscale nitrobenzene oxidation method (Yamamura et al 2010(Yamamura et al , 2011. The GC-MS analysis of the nitrobenzene oxidation products showed that lignin in each organ consisted of guaiacyl, syringyl, and p-hydroxyphenyl units (Table 2), consistent with the result of thioacidolysis.…”
Section: Lignin Structures Of E Ravennaementioning
confidence: 63%
“…The aromatic substitution patterns of the β-O-4 substructure and also other substructures were analysed by alkaline nitrobenzene oxidation (Yamamura et al 2010(Yamamura et al , 2011.…”
Section: Lignin Aromatic Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the lignin aromatic components not only of β-O-4 substructure which is obtained by the thioacidolysis but also of other substructures, each organ of J. curcas was analyzed by the microscale nitrobenzene oxidation method (Yamamura et al 2010(Yamamura et al , 2011. GC-MS analysis of the nitrobenzene oxidation products indicated that the molar ratios of syringyl to guaiacyl moieties (S/V), as measured by that of syringaldehyde to vanillin, varied among organs (Table 1).…”
mentioning
confidence: 99%
“…Secondary xylem of a one-year-old stem of the plant was also analyzed by the thioglycolic acid method. First, each sample was subjected to thioacidolysis (Nakatsubo et al 2008;Yamamura et al 2011) to confirm the presence of lignin by identifying phenyltrithioethylpropane compounds (Figure 2), which are derived speci cally from β-O-4 substructures of lignin polymers. The detection of the diagnostic monomers clearly indicated the presence of lignin in all analyzed samples (Figure 3).…”
mentioning
confidence: 99%